PERAN MASJID SEBAGAI SARANA PENDIDIKAN NONFORMAL UNTUK MENINGKATKAN AKHLAK REMAJA KELURAHAN LABUHAN DELI KECAMATAN MEDAN MARELAN - Mhd. Ayub (Fakultas Agama Islam, 2021)
The role of the Mosque as a Non-Formal Islamic Education Facility at the Dja'faar Warrahmah Mosque, Labuhan Deli Village, Medan Marelan District, among others, overall, the mosque takmir in collaboration with mosque youth is able to play a role in making the Dja'faar Warrahmah Mosque a non-formal Islamic education institution by providing guidance to the people in particular the community. on Jalan Young Panah Hijau, Environment VII, Labuhan Deli Sub-district, Medan Marelan District, held several non-formal Islamic educations, such as cults at dawn and sunset, youth studies after sunset prayers, Al-Qur'an Education Park (TPQ), recitations for women at ta'lim majlis which is held regularly 4 times a month and also incidental recitations, such as the commemoration of the birthday of the Prophet and Isra 'Mi'raj, mainly to meet the mental-spiritual needs of the people. The positive impact of non-formal education at the Dja'faar Warrahmah mosque, especially for the development of adolescent morals, occurs a lot changes from teenagers, many were initially very concerned because teenagers don't really understand religion, even these teenagers often do negative things, such as getting drunk, stealing, and speeding on the road. After holding positive activities about moral education such as the recitation, the teenager did more positive things, it could even be said that the teenager had a pretty good character, because teenagers could already see it.